Radiation exposure facilities for radiobiology in Europe: availability, capabilities, and limitations - Unterleiter, Tom; Shariff, Maya; Rückert, Michael; Winterling, Lena; Ruspeckhofer, Laura; Weissmann, Thomas; Putz, Florian; Fietkau, Rainer; Bert, Christoph; Gaipl, Udo; Deloch, Lisa (Radiation and Environmental Biophysics, 2025)
Experimental radiobiology studies rely on exposure platforms that replicate real-world scenarios, yet information on their availability and biological suitability is often fragmented. We thus aimed to map capabilities, access routes, and limitations of European irradiation facilities, with a focus on Germany and briefly contextualized it with selected platforms in the United States of America (U.S.). Single-source systems (X-ray, gamma, alpha/beta) are widely available for cell/animal work, but mixed-beam platforms with controlled conditions and traceable dosimetry are scarce and oversubscribed while alpha/radon analogue setups vary in geometry and atmosphere control, hindering comparability. Large user facilities (reactors, cyclotrons, space-simulation) offer powerful modalities but often lack clearly documented biological access procedures. Here, the selected U.S. facilities provide more explicit user pathways (proposal, fee-for-service, programmatic access). Priorities for Europe should thus include standardized, incubator-compatible mixed-beam systems; a more harmonized reporting of dosimetry/environmental parameters; and a better visibility of biological access in infrastructure catalogues. Ongoing coordination initiatives can underpin these improvements, strengthening reproducibility and access.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Alpha-Radiation; Experimental setups; Mixed-Beam; Radiation protection; Radiation research; Radon